PREVALENSI PEROKOK DILINGKUNGAN MAHASISWA PGSD UTM - Mahmud Abdul Rauf (Widyagogik, 2015)
Smoking is an activity sucking and wafting smoke from mouth and nose by burning roll of tobacco name cigarette. Smoke from cigarette can be waft by other people near smokers. Almost research says, that smoking had bad effect for health and some research shows that smoking habbit can reduce working ability. This research, by using descriptive quantitative method try to describe smoking prevalencies at PGSD Trunojoyo University college student, describe their social economy charactertic and the impact to their economic and studies goals. The result of this research shows only nine percent PGSD College Student in Trunojoyo University had smoking habbit. If we compare with college student hadn’t smoke, there are less alocated money for food and also for buying books for support they studies. They cummulatife prestation indexs (IPK) less than non smoking college student